Independent Oil Palm Smallholder Farmers; Household Income, Consumption, and Sustainability Challenges - Erwin Candra; Syaiful Hadi; Novia Dewi; Rizqi Sari Anggraini (Jurnal Agribisnis, 2021)
Riau Province is the largest producer of palm oil in Indonesia, with more than 2.4 million hectares of land used for oil palm plantation The province of Riau is the largest producer of palm oil in Indonesia, with more than 2.4 million hectares of land used for palm oil plantations. In 2017, 792,970 farmers were involved in an oil palm plantation, which played a significant role in economic growth in rural areas of the Riau Province. Independent Smallholder plantations account for 56.84% of total oil palm plantation areas. However, issues related to unsustainable production including environmental, social, and legal issues are still the most pressing issues to access the global market. The objective of this study is to analyze the household and consumption of Independent Smallholder Farmers and their challenges for sustainability issues. The population of this study is independent oil palm smallholder farmers in Riau Province. The sample size was 270 farmers and chosen randomly from 27 subdistricts from 3 Districts in Riau Province (30 farmers for each subdistrict respectively). The study found that 59.36 percent of the farmer's Households were from oil palm plantation and 48.71 percent of the farmer’s consumption monthly expenditure was for foods. The sustainability challenges faced by the Independent Smallholders Farmer were Uncertified seed, Land legalities, no farmers group, and no management and environmental monitoring make it difficult for independent smallholders farmers to meet ISPO standards. To improve farmer,s capacity to meet and comply with the ISPO standards, external supports from the government and private sectors are needed.